{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

2.6 Dual Spaces 2

# 2.6 Dual Spaces 2 - 2.6 Trapezoidal rule R b a p t dt ≈ b...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 2.6. Trapezoidal rule - R b a p ( t ) dt ≈ ( b- a ) f ( b )+ f ( a ) 2 Simpson’s rule - R b a f ( t ) dt ≈ ( b- a ) 6 ( f ( a ) + 4 f ( a + b 2 ) + f ( b )) 11. For ∀ x ∈ V, x 7→ ψ 2 T ( x ) = [ T ( x ) x 7→ T tt ψ 1 ( x ) = T tt ( b x ) = b xT t To show commuting, [ T ( x ) = b xT t in W ** : W * → F ∀ g ∈ W * , i.e. g : W → F a linear functional Show ( b xT t )( g ) = [ T ( x )( g ) [ T ( x )( g ) = g ( T ( x )) = ( gT )( x ) = widehatx ( gT ) = b x ( T t g ) = b xT t ( g ) ∴ ψ 2 T = T tt ψ 1 12. ψ ( β ) = β ** β = { x 1 ,x 2 , ··· ,x n } a basis for V ⇒ β * = { x * 1 ,x * 2 , ··· ,x * n } a basis for V * , where x * i : V → F a linear functional s.t. f i ( x j ) = δ ij Since V ** is the dual space of V * ∃ β ** = { x ** 1 ,x ** 2 , ··· ,x ** n } a basis for V ** s.t. x ** i : V * → F * linear functional s.t. x ** i ( x * j ) = δ ij Show x ** i = b x i , ∀ i, ψ ( β ) = { x 1 ,x 2 , ··· ,x n } b x ( x * i ) = δ ij = x ** i ( x * j ) , ∀ i,j 130 PNU-MATH 2.6....
View Full Document

{[ snackBarMessage ]}

### Page1 / 6

2.6 Dual Spaces 2 - 2.6 Trapezoidal rule R b a p t dt ≈ b...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online